HUBUNGAN PENGETAHUAN TENTANG STROKE DENGAN PERILAKU PENCEGAHAN PADA MASYARAKAT DUSUN DONOLAYAN DONOHARJO SLEMAN YOGYAKARTA - Patria Asda; Nasiatul Aisyah Salim; Joni H. Lapaibel (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2018)
Background: The knowledge and preventive behaviors toward stroke must be associated because this disease is often called as “CVA (Cerebrovascular Accident)”. Stroke is the third leading cause of death in the world. 15 million people worldwide suffer a stroke, one-third of them die and the rest is left permanently disabled. Indonesia Basic Health Research in 2013 especially in Special Region of Yogyakarta (DIY) shown that stroke is the second leading non-communicable disease in DIY. Data of stroke recorded in Public Health Ofﬁ ce in Sleman in 2015 indicated that the highest number was 1.325 cases. Data of Community Health Center (PUSKESMAS) in Ngaglik II in 2015 shown that there were 142 stroke cases occurred, and the highest was in Donoharjo with 62 people spread in all villages, and the leading case was in Donolayan village with 8 people. Objectives: To ﬁ nd out the level of knowledge about stroke, preventive behaviors, and the association between the knowledge about stroke and the preventive behaviors in communities of Donolayan Donoharjo Sleman Yogyakarta. Methods: The method used in this research is quantitative with cross sectional design. The respondents participated in this research are 64 people aged 40-60 years old in Donolayan village. The sampling technique employed is total sampling, and the data processing used in this research is Chi-square.Results: The result indicated that the level of knowledge in communities about stroke was 54 people (84,4%), and the preventive behaviors of stroke were 50 people (78,1%), and there was a signiﬁ cant relation known sig (2-sided) 0,033<0,1 with correlation coefﬁ cient value 0,281.Conclusion: There was a signiﬁ cant relation between the knowledge about stroke and the preventive behaviors of stroke in communities of Donolayan Donoharjo Sleman Yogyakarta. Therefore, the better the knowledge of respondents have, the better the preventive behaviors of respondents obtain.